Attempted suicide and violent criminality among Danish second-generation immigrants according to parental place of origin. (March 2016) - Webb, Roger T; Antonsen, Sussie; Pedersen, Carsten B; Mok, Pearl LH; Cantor-Graae, Elizabeth; Agerbo, Esben
Background: Immigrant populations in Western European countries have grown in their size and diversity, but little is known about risks of self-directed and externalised violence among second-generation immigrants. Aims: To compare risks for attempted suicides and violent offending among second-generation immigrants to Denmark according to parental region of origin versus the native Danish population. Methods: Data from interlinked national Danish registers were used ( N  = 1, 973, 614). Parental origin outside Denmark was categorised thus: Asia, Africa, Middle East, Greenland, other Scandinavian countries, elsewhere in Europe and all other regions. We estimated gender-specific cumulative incidence and incidence rate ratios (IRRs) versus native Danes. Results: In virtually all subgroups of second-generation immigrants, risk was elevated for the two adverse outcomes in both genders. Females generally had greater elevations in attempted suicide risk, and males had greater elevations in violent offending risk. For attempted suicide, especially large IRRs were observed for males and females whose parents emigrated from Greenland; for violent offending, risks were particularly raised for males and females of Middle Eastern, Greenlandic and African origin. Adjustment for socioeconomic status partially explained these associations. Conclusion: Western European nations should develop preventive programmes tailored towards specific second-generation immigrant populations, with integrated approaches jointly tackling suicidality and violence.